Effects of Life-Long Exercise on Age-Related Inflammation, Apoptosis, Oxidative Stress, Ferroptosis Markers, and NRF2/KAEP 1/Klotho Pathway in Rat Kidneys - Yuan, Xi-Kun; Ni, Pin-Shi; Yan, Zhen-Hao; Yu, Zhi; Wang, Zhuang-Zhi; Zhang, Chen-Kai; Li, Fang-Hui; Yu, Xiao-Ming (Physiological research, 2024)
Xi-Kun Yuan Pin-Shi Ni Zhen-Hao Yan Zhi Yu Zhuang-Zhi Wang Chen-Kai Zhang Fang-Hui Li Xiao-Ming Yu 1Sports Department, Nanjing University of Science and Technology ZiJin College, Nanjing, China, 2School of Sport Sciences, Nanjing Normal University, Nanjing, China, 3Shanghai Seventh People's Hospital, Shanghai, China To investigate the effects of life-long exercise (LLE) on age-related inflammatory cytokines, apoptosis, oxidative stress, ferroptosis markers, and the NRF2/KAEP 1/Klotho pathway in rats. Eight-month-old female Sprague-Dawley rats were divided into four groups: 1) LLE: 18-month LLE training starting at 8 months of age, 2) Old moderate-intensity continuous training (OMICT): 8 months of moderate-intensity continuous training starting at 18 months of age, 3) Adult sedentary (ASED): 8 month-old adult sedentary control group, and 4) Old sedentary (OSED): a 26-month-old sedentary control group. Hematoxylin eosin staining was performed to observe the pathological changes of kidney tissue injury in rats; Masson's staining to observe the deposition of collagen fibers in rat kidney tissues; and western blotting to detect the expression levels of IL-6, IL 1beta, p53, p21, TNF-alpha, GPX4, KAEP 1, NRF2, SLC7A11, and other proteins in kidney tissues. Results: Compared with the ASED group, the OSED group showed significant morphological changes in renal tubules and glomeruli, which were swollen and deformed, with a small number of inflammatory cells infiltrated in the tubules. Compared with the OSED group, the expression levels of inflammation-related proteins such as IL-1beta, IL-6, TNF alpha, and MMP3 were significantly lower in the LLE group. Quantitative immunofluorescence analysis and western blotting revealed that compared with the ASED group, KAEP 1 protein fluorescence intensity and protein expression levels were significantly enhanced, while Klotho and NRF2 protein fluorescence intensity and protein expression levels were reduced in the OSED group. Compared with the OSED group, KAEP 1 protein fluorescence intensity and protein expression levels were reduced in the LLE and OMICT groups. Klotho and KAEP 1 protein expression levels and immunofluorescence intensity were higher in the LLE group than in the OSED group. The expression levels of GPX4 and SLC7A11, two negative marker proteins associated with ferroptosis, were significantly higher in the LLE group than in the OSED group, while the expression of p53 a cellular senescence-associated protein that negatively regulates SLC7A11, and the downstream protein p21 were significantly decreased. LLE may ameliorated aging-induced oxidative stress, inflammatory response, apoptosis, and ferroptosis by regulating Klotho and synergistically activating the NRF2/KAEP 1 pathway. Keywords: Life-long exercise, Moderate intensity continuous training, Aging, Kidney tissue, Ferroptosis.
Keywords: ledviny; apoptóza; biologické markery; Glucuronidase; faktor 2 související s NF-E2; stárnutí; Apoptosis; Kidney; Oxidative Stress; Female; kondiční příprava zvířat; krysa rodu Rattus; Physical Conditioning, Animal; Signal Transduction; potkani Sprague-Dawley; glukuronidasa; Inflammation; signální transdukce; zánět; Rats, Sprague-Dawley; Biomarkers; zvířata; ženské pohlaví; Aging; oxidační stres; Rats; Animals; proteiny Klotho; NF-E2-Related Factor 2; Klotho Proteins; Ferroptosis; ferroptóza